Influence of stabilising agents and pH on the size of SnO2 nanoparticles - Rac, Olga; Suchorska-Woźniak, Patrycja; Fiedot, Marta; Teterycz, Helena (Beilstein Journal of Nanotechnology, 2014)
According to recent research, the use of nanoparticles as a gas-sensitive material increases the selectivity and sensitivity and shortens the response time of a sensor. However, the synthesis of SnO2 nanoparticles presents many difficulties. The following article presents a simple and inexpensive method for the synthesis of SnO2 nanoparticles. The influence of the surfactant and polymer choice on the size of the resulting nanoparticles was investigated and a mechanism describing their interaction was proposed. It was found that stable colloids of SnO2 nanoparticles are formed in the presence of both PEI and Triton X-100 surfactants as stabilising agents. However, an additional factor essential for good stabilisation of the nanoparticles was an appropriate acidity level of the solution. Under optimal conditions, nanoparticles having an average diameter of about 10 nm are reproducibly formed.
Keywords: nanoparticles; polyethylenimine; polyvinylpyrrolidone; surfactant; tin dioxide